(untitled) (Research, Society and Development, 2020)
This paper is a literature review, held between june 2019 and may 2020, dedicated to analyze articles published in the last decade, about the relevance of the Surgeon-Dentist as a member of the multidisciplinary team in the hospital environment, seeking to report the arguments used by authors who justify the insertion of this professional, and the reason why he is necessary to improve the quality of life of hospitalized patients. Method: Search carried out in the Pubmed®, Scielo, Medline and LILACS databases, discarding articles that were not available in full or whose approach was distant from the proposed theme. Conclusion: This study found that the presence of the Surgeon-Dentist, as a member of the multidisciplinary team in the hospital environment is essential to the maintenance and restoration of the patients’ health, since the prevention, diagnosis and treatment of pathologies that affect the oral environment are competence of this professional, and its insertion integrated with the other health professionals make it possible to decrease the length of hospital stay, and the implementation of positive health practices.